2021
DOI: 10.1177/01455613211056543
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Body Dysmorphic Disorder Among Rhinoplasty Candidates: A Systematic Review

Abstract: Objective Body dysmorphic disorder (BDD) represents a bridge between the fields of psychiatry and cosmetic surgery. It is a psychiatric disorder involving altered body image and has been associated with cosmetic surgery. Many studies have investigated BDD following rhinoplasty. However, their findings were inconsistent, which prompted us to conduct this systematic review to obtain strong evidence about the prevalence of BDD among rhinoplasty candidates. Methods We searched the literature using electronic datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…66,67 Finally, the importance of evaluating the psychology of patients is beginning to come into the forefront of surgery, in particular with cosmetic rhinoplasty with a significant amount in the literature examining body dysmorphic disorder. 68,69 The development of new screening tools such as the Body Dysmorphic Disorder Questionnaire-Aesthetic Surgery (BDDQ-AS) have sought to identify these patients preoperatively for effective counseling on surgical expectations. 70 With the prevalence of underlying psychiatric disorder within the general population on the rise, these are certainly considerations that will require more attention moving forward.…”
Section: New Horizonsmentioning
confidence: 99%
“…66,67 Finally, the importance of evaluating the psychology of patients is beginning to come into the forefront of surgery, in particular with cosmetic rhinoplasty with a significant amount in the literature examining body dysmorphic disorder. 68,69 The development of new screening tools such as the Body Dysmorphic Disorder Questionnaire-Aesthetic Surgery (BDDQ-AS) have sought to identify these patients preoperatively for effective counseling on surgical expectations. 70 With the prevalence of underlying psychiatric disorder within the general population on the rise, these are certainly considerations that will require more attention moving forward.…”
Section: New Horizonsmentioning
confidence: 99%
“…For preoperative evaluation of rhinoplasty patients, the BDD concern questionnaire‐aesthetic version (BDDQ‐AS) has been developed, culturally adapted, and validated in this patient population and different languages 8–10 . Despite the high prevalence of BDD and its association with higher levels of depression and anxiety, the prevalence of these psychiatric conditions in rhinoplasty patients is understudied 11,12 and their effect on rhinoplasty outcomes and QoL remains unclear 6,13–17 …”
Section: Introductionmentioning
confidence: 99%
“…6 However, the prevalence is known to be higher in a clinical setting and especially in rhinoplasty candidates. 4,[7][8][9][10][11][12][13][14] According to a meta-analysis from Nabavizadeh et al, the pooled prevalence for BDD was 32.7% in rhinoplasty candidates. 6 AlAwadh et al found a preoperative prevalence of BDD ranging from 22 to 52% in publications between 2016 and 2021.…”
mentioning
confidence: 99%
“…6 AlAwadh et al found a preoperative prevalence of BDD ranging from 22 to 52% in publications between 2016 and 2021. 10 The wide range in prevalence rate in various studies is most likely due to differences in population but also in the interpretation and application of the diagnostic criteria for BDD. 15 The gender ratio is reported as equal, although some studies have found a slight preponderance in women.…”
mentioning
confidence: 99%